DAMPAK AJARAN TRI HITA KARANA TERHADAP KARAKTER SISWA DI SMP NEGERI 1 BANGLI - Ni Wayan Arini; Ni Wayan Widyani; I Made Putra Aryana (Guna Widya: Jurnal Pendidikan Hindu, 2023)
Humans need harmony in their lives; harmony relationship with God, humans, and the environment. This teaching in Hinduism is called Tri Hita Karana consisting of 1) Parahyangan,; a harmonious relationship between humans and the Almighty God (Sang Hyang Widhi Wasa), 2) Pawongan; a harmonious relationship between humans and fellow human beings and 3) Palemahan; a harmonious relationship between humans and natural environment. The teacher does not only provide knowledge to students, but in learning it is also interspersed with giving advice so that students have good character, such as being religious, socially concerned, environmentally concerned and disciplined when the teacher explains the material. Therefore, students are not only smart in terms of knowledge, but also have good character and attitude. Through Hindu Religious and Moral Education, students can find out various Hindu religious teachings which are very effectively implemented to be able to develop their character. The implementation of learning in the classroom is related to the concept of Tri Hita Karana teachings. Because of the Tri Hita Karana learning material, students have an understanding of Tri Hita Karana teachings before applying them in their daily life, especially at school. Whereas in an effort to develop student character outside the classroom, Hindu Religious and Moral Education teachers invite students to implement the Tri Hita Karana teachings that have been obtained in class in the form of the practice of making ceremonies at Padmasana schools as students' psychomotor values and implementation in the form of attitudes that show good character in himself related to the teachings of Parahyangan, Pawongan and Palemahan in the school environment. The impact of implementing the teachings of Tri Hita Karana on the character development of students at SMP Negeri 1 Bangli is as follows: developing student character, increasing student awareness to carry out their religious teachings, increasing awareness of students towards others, increasing student awareness to the environment, and creating harmony.